PRICE, INNOVATION, AND BRAND IMAGE'S EFFECT ON CUSTOMER SATISFACTION AT AGUNG TAILOR PURWODADI SEWING UMKM - Fitria Enno Apriliyani; Sri Martono (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2025)
Background & Purpose: Analyzing how pricing, innovation, and brand image affect customer happiness is the goal of this study. Regarding this issue, UMKM Agung Tailor refers the difference between customer expectations and the reality they experience. Method: Quantitative research methodology is employed. Total sampling is the method used in this study. In this study, there were 97 responders in the sample. The tool used to collect the data is a questionnaire. Results: demonstrates how Sewing UMKM's brand image influences customer satisfaction in a positive and significant way, how innovation influences customer satisfaction in a positive and significant way, and how price influences customer satisfaction in a positive and significant way. Purwodadi Agung Tailor. Conclusion & Suggestion: The variables brand image, innovation, price customer satisfaction, in the UMKM Jahit Agung Tailor Purwodadi, overall product prices have an influence, but digital marketing does not have a real influence. When creating marketing strategies that influence consumer purchasing decisions, selling price and product quality must be considered simultaneously, and digital marketing methods may need to be reevaluated.